Mathematical support for solving the classification problem using neural network algorithms - et. al., D T Mukhamedieva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article considers the problem of increasing the efficiency of solving the classification of an unknown object in a neural network algorithm in the case of a data set. In such cases, it is important to select the number of neurons in the neural network layers and adjust the parameters to redistribute the errors. The mathematical apparatus and algorithm of the neural network in solving the classification problem are given in detail, and the results are analyzed using model problems.